PRELIMINARY PHYTOCHEMISTRY ASSESSMENT OF Heliconia rostrata AND THE POTENTIAL INHIBITORY ACTIVITY OF SOME EFFECTS OF THE Bothrops asper (mapanà X) VENOM. - ESTRADA G., Sebastián; QUINTANA, Juan C.; JIMENÉS, Silvia L.; Alarcón P., Juan C.; PEREAÑEZ J., Jaime A.; VARGAS, Leidy J. (Vitae, 2009)
Some Heliconiaceae family species, had demonstrated to be effective neutralizing partial or totally the lethal, indirect hemolytic, hemorrhagic, proteolytic, clotting, miotoxic and edema-forming activities from the Bothrops asper (mapaná equis) venom. This work evaluates two species of heliconias: Heliconia psittacorum and Heliconia rostrata against the indirect hemolytic, proteolytic and clotting activities induced by B. asper without any inhibitory effect on the indirect hemolytic and proteolytic effects. On the contrary, the extracts retard the venom clotting effect with regard to the positive control up to 45.59 seconds. In the electrophoretic profile a band belonging to the H. psittacorum is observed, moreover a decrease and increase in the intensity of some bands (66 y 31 KDa respectively) possibly indicate its degradation by the extracts. The phytochemical evaluation of the extracts shows the presence of primary metabolites as glucids and proteins; and secondary metabolites as phenolics compounds, terpenoides and cumarins, some of them reported in others vegetal species as responsible of the anti-ophidian activity.